Convergence theorems of a modified hybrid algorithm for a family of quasi-φ-asymptotically nonexpansive mappings - Zhou, Haiyun; Gao, Gailiang; Tan, Bin (Journal of applied mathematics & computing, 2010)
The purpose of this article is to propose a modified hybrid projection algorithm and prove strong convergence theorems for a family of quasi- φ -asymptotically nonexpansive mappings. The results of this paper improve and extend the results of S. Matsushita and W. Takahashi (J. Approx. Theory, 134: 257–266 ( 2005 )), T.H. Kim, H.K. Xu (Nonlinear Anal. 64: 1140–1152 ( 2006 )), Y.F. Su, D.X. Wang, M.J. Shang (Fixed Point Theory Appl. 2008: 284613 ( 2008 )) and others.